2021
DOI: 10.31246/mjn-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Fulfilment of minimum acceptable diet (MAD), short birth length and family income level are associated with stunting in children aged 6-23 months in Central Jakarta

Abstract: Introduction: Stunting is a condition characterised by retardation in the growth and development of children as a result of chronic inadequate nutritional intake and/or recurrent infectious diseases. This research aims to determine the factors related to stunting occurrence among children aged 6-23 months. Methods: This cross-sectional study was carried out in 2019. The sample was 231 children selected by multistage random sampling technique from 13 Posyandu (integrated healthcare centres) in six administrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This finding further supported by a prior systematic review that identified exclusive breastfeeding as a significant protective factor against stunting in children under five years old (Rachmayanti et al, 2022). When it comes to complementary feeding and poor-quality food consumption, infrequent feeding, poor micronutrient intake, and low dietary diversity have emerged as predictors elevating stunting risk (Hijra et al, 2016;Madinar et al, 2021;Nurhayati et al, 2020). Our findings consolidate several studies that have identified associations between feeding practices and the incidence of stunting in Indonesia, a pattern previously highlighted by Beal et al (2018) in their review focusing on children aged 6-59 months.…”
Section: Inadequate Breastfeeding Complementary Feeding and Poor-qual...supporting
confidence: 66%
See 2 more Smart Citations
“…This finding further supported by a prior systematic review that identified exclusive breastfeeding as a significant protective factor against stunting in children under five years old (Rachmayanti et al, 2022). When it comes to complementary feeding and poor-quality food consumption, infrequent feeding, poor micronutrient intake, and low dietary diversity have emerged as predictors elevating stunting risk (Hijra et al, 2016;Madinar et al, 2021;Nurhayati et al, 2020). Our findings consolidate several studies that have identified associations between feeding practices and the incidence of stunting in Indonesia, a pattern previously highlighted by Beal et al (2018) in their review focusing on children aged 6-59 months.…”
Section: Inadequate Breastfeeding Complementary Feeding and Poor-qual...supporting
confidence: 66%
“…This condition is often an indicator of inadequate fetal growth and can result from factors such as poor maternal nutrition, maternal health problems, and placental insufficiency (Gonete et al, 2021;Jamshed et al, 2020). Furthermore, a study revealed that 23% of children with short birth length children also had low birth weight (Madinar et al, 2021), further underscoring the interconnectedness of these predictors.…”
Section: Child Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Another 720 articles were excluded following the PRISMA-ScR flow diagram (see Figure 1). Of 27 studies, the predictors of stunting have been widely studied in Indonesia (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) . Other Southeast Asian countries that have also studied the predictors of stunting are the Philippines (24)(25)(26)(27)(28)(29) , Cambodia (30)(31)(32) , Vietnam (33)(34) , Myanmar (35)(36) , Malaysia (37)(38) , and Brunei Darussalam (39) .…”
Section: Resultsmentioning
confidence: 99%
“…Other Southeast Asian countries that have also studied the predictors of stunting are the Philippines (24)(25)(26)(27)(28)(29) , Cambodia (30)(31)(32) , Vietnam (33)(34) , Myanmar (35)(36) , Malaysia (37)(38) , and Brunei Darussalam (39) . From our defined population, few studies appear to have specifically studied the predictors of stunting in children aged 6-24 months only (19)(20)(27)(28)(31)(32)(33)(35)(36) and/or have also examined the caregiver or household of children (15,(24)(25)(29)(30)34) . Regarding the study designs used, secondary data analysis (14/27 studies) is the most widely used study design.…”
Section: Resultsmentioning
confidence: 99%